English Teachers’ Pedagogical Competence in Regard to Planning the Teaching and Learning Process - Hasriani G, Hasriani G (JOLLT Journal of Languages and Language Teaching, 2022)
This research aimed at identifying the English teachers’ pedagogical competence in planning the teaching and learning process. The profile of English teachers’ pedagogical competence in planning the teaching and learning process was based on the National Standard of Education, in section 28, sub-section 3 point a. The researcher employed descriptive evaluative method. The subjects of this research were four English teachers from different schools of Madrasah Aliyah in Kabupaten Enrekang. The purpose of the research was to describe the teachers’ pedagogical competence in planning the teaching and learning process. Based on the result and discussion, the four teachers had different quality in terms of pedagogical competence in planning the teaching and learning process. The scores of the teachers were: teacher 1 = 4 (very good), teacher 2 = 3 (good), teacher 3 = 3 (good), and teacher 4 = 3 (good). Based on the result and discussion, it could be concluded that the four teachers had good quality in terms of pedagogical competence in regard to planning the teaching and learning process. The four teachers realized the importance of the arrangement of lesson plan before teaching the students in the classroom.